Quando o acompanhamento terapêutico encontra a escola: a construção de uma prática intercessora - Albano, Paula Buainain (2015)
The present research aims in studying the issue of therapeutic accompaniment as a support device to the inclusion of children with special educational needs in the regular education system. From a clinical, political, critical and institutionalist reading of the therapeutic accompaniment of children in schools, conducted with Grupo Laço, a group that supports school inclusion projects, we discussed the specificities of this modality of treatment: the demands and functions which are met at school, the effects that the presence of a therapeutic accompaniment produces in the actors involved and the main points of tension that permeate the work. We show the methodological design of this practice, which we call intercessory because it seeks to promote the neighborhood spaces between people with distinct experiences that enter in the trade relations, without priority or inferiority between the knowledges. This methodology is characterized by a comanagement work process, lateralized, in which all actors play an active roll in the inclusion project: therapeutic accompaniment, educators, parents and children, in order to build a common plan. The methodology is also comprised of the work with the crisis and in the crisis, as well as the inclusion of the effects produced in the work process. For this, we rely on concept-tools of the institutional analysis, we employ some reflections on the therapeutic accompaniment clinic, which is applied to the school field and about the school inclusion field itself, especially the discussions about the difference and equality and the principles of inclusion, which contrast with the integration, aligned with the standardization processes